Pemberdayaan Kader Kesehatan dalam Program Pemantauan Pertumbuhan dan Perkembangan Anak Balita di Kecamatan Mengwi Tahun 2018 - Ni Wayan Armini (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2019)
Disruption of developmental delays is a serious problem for countries in the world. In Indonesia, the prevalence of developmental disorders varies from 12.8% to 16%, so it is recommended to have growth observation/screening for each child. Health cadres have a very important role because they are health workers in the midst of society. Given the importance of todlers’ optimal growth and development process, one of the activities that can be carried out is by organizing health cadre’s empowerment in monitoring the growth and development of children under five. Method: training and guidance using question and answer, practice, demonstration, problem solving, discussion, pretest and posttest. Results: Statistical tests found that there is a significant differences in knowledge of respondents before and after training and guidance (p value 0.001). Then found significant differences in attitudes before and after training and guidance (p value 0.029). There are also significant differences in the skills of respondents before and after training (p value 0.001). Suggestion: public health center had been suggested to continue training and guidance activities on periodic monitoring of toddlers' growth and development programs for health cadres.Keywords: growth, development, toddler, training and guidance, Health cadres.Disruption of developmental delays is a serious problem for countries in the world. In Indonesia, the prevalence of developmental disorders varies from 12.8% to 16%, so it is recommended to have growth observation/screening for each child. Health cadres have a very important role because they are health workers in the midst of society. Given the importance of todlers’ optimal growth and development process, one of the activities that can be carried out is by organizing health cadre’s empowerment in monitoring the growth and development of children under five. Method: training and guidance using question and answer, practice, demonstration, problem solving, discussion, pretest and posttest. Results: Statistical tests found that there is a significant differences in knowledge of respondents before and after training and guidance (p value 0.001). Then found significant differences in attitudes before and after training and guidance (p value 0.029). There are also significant differences in the skills of respondents before and after training (p value 0.001). Suggestion: public health center had been suggested to continue training and guidance activities on periodic monitoring of toddlers' growth and development programs for health cadres. Keywords: growth, development, toddler, training and guidance, Health cadres.